Unified power converters for battery charging and traction drive systems for electric vehicles: cost and performance analysis - Sousa, Tiago José Cunha (2019)
Electric vehicles (EVs) are a promising solution to mitigate the emission of greenhouse gases and atmospheric pollution. Although EVs existence spans from more than one century, only in the recent years there has been a considerable development in the electric mobility paradigm. This development is also verified in the operation modes for the EV, giving it an important role in smart grids. Moreover, the implementation of unified power converters for battery charging and traction drive systems is also a key topic about EVs, allowing at the same time a hardware reduction and an increasing in its functionalities. However, no economic studies about the practical feasibility of these unified systems for EVs have been reported in the literature. In this context, this paper presents a cost assessment of unified battery charging and traction drive systems for EVs focusing on practical aspects. An economic comparison is performed between a traditional EV and a unified system in order to attain a cost/performance analysis for the unified power converters that can be used in EVs.